2019
DOI: 10.1016/j.neuron.2019.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Universal Transform or Multiple Functionality? Understanding the Contribution of the Human Cerebellum across Task Domains

Abstract: An impressive body of research over the past 30 years has implicated the human cerebellum in a broad range of functions, including motor control, perception, language, working memory, cognitive control, and social cognition. The relatively uniform anatomy and physiology of the cerebellar cortex has given rise to the idea that this structure performs the same computational function across diverse domains. Here we highlight evidence from the human neuroimaging literature that documents the striking functional he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
212
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(226 citation statements)
references
References 96 publications
(115 reference statements)
13
212
0
1
Order By: Relevance
“…Our open-source computational modeling pipeline [7] confirmed that the magnitude of the electric field for Celnik montage [13] primarily targeted the pontocerebellum as postulated in the experimental paper by Jayaram et al [10]. The innovation lies not only in the ability to optimize the lobular electric field in the cerebellum [7] but also in the augmented approach to address functional heterogeneity [58] based on the outcomes from a task battery. Here, post-stroke deficits can cover multiple task domains that can be elucidated with multi-domain behavioral experiments (e.g., FRT balance function, hand function, gait function, cognitive function) to develop an appropriate objective function for ctDCS optimization that addresses cerebellar multiple functionalities [58].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our open-source computational modeling pipeline [7] confirmed that the magnitude of the electric field for Celnik montage [13] primarily targeted the pontocerebellum as postulated in the experimental paper by Jayaram et al [10]. The innovation lies not only in the ability to optimize the lobular electric field in the cerebellum [7] but also in the augmented approach to address functional heterogeneity [58] based on the outcomes from a task battery. Here, post-stroke deficits can cover multiple task domains that can be elucidated with multi-domain behavioral experiments (e.g., FRT balance function, hand function, gait function, cognitive function) to develop an appropriate objective function for ctDCS optimization that addresses cerebellar multiple functionalities [58].…”
Section: Discussionsupporting
confidence: 57%
“…We postulate that ctDCS optimization should be based on deficits in functional outcomes during quantitative multi-task evaluation due to cerebellar multiple functionalities [58] where ctDCS optimization can be based on mapping to universal cerebellar computations [58], e.g., relate to the executive cluster of the CCAS [59] in IMA. Importantly, King et al recently showed that lobular boundaries commonly used to summarize functional data do not coincide with functional subdivisions [57].…”
Section: Regression Analysis Of the Electric Field Distribution Withmentioning
confidence: 99%
“…A similar debate is ongoing in General factors and the cerebellum 50 the psychology literature about concept proliferation and confusion known as the "jingle and jangle fallacies", the former being the error of referring to different constructs by the same name and the latter the error of referring to the same construct by different names (Lilienfeld et al, 2015). A debate currently exists specifically in the cerebellar literature as to whether the cerebellum performs the same computational function across domains such as a Universal Cerebellar Transform or performs multiple functions consisting of functionally distinct computations (Diedrichsen, King, Hernandez-Castillo, Sereno, & Ivry, 2019;Guell, Gabrieli, & Schmahmann, 2018a). The cerebellum is associated with pretty much all psychological functions and evidence has demonstrated similar topographic organisation to the cortex (Manni & Petrosini, 2004), even to the retinotopic level (van Es, van der Zwaag, & Knapen, 2019).…”
Section: Part 3: Synthesismentioning
confidence: 99%
“…This notwithstanding, neuroimaging studies using these modalities play a pivotal role in elucidating the functional role of the cerebellum by unraveling its contribution to numerous tasks such as motor control, visually guided behavior and many cognitive tasks (Buckner, 2013). Because they monitor the activity of the whole brain simultaneously, these imaging techniques are also used to examine the involvement of the cerebellum in potential large-scale cerebral networks and to assess the functional-role of cerebellar-thalamo-cortical pathways (Diedrichsen et al 2019). Nevertheless, the relatively sluggish nature of haemodynamic and metabolic responses remains a severe limitation when it comes to investigating the precise temporal properties of cerebellar activity.…”
Section: Introductionmentioning
confidence: 99%